Regular Statin Use and Incidence of Postendoscopic Retrograde Cholangiopancreatography Pancreatitis. Issue 10 (November 2020) - Hakuta, Ryunosuke; Nakai, Yousuke; Hamada, Tsuyoshi; Suzuki, Yukari; Inokuma, Akiyuki; Oyama, Hiroki; Kanai, Sachiko; Nakamura, Tomoka; Sato, Tatsuya; Ishigaki, Kazunaga; Saito, Kei; Saito, Tomotaka; et al.
Abstract : Goals and Background: Endoscopic retrograde cholangiopancreatography is widely utilized to diagnose and treat various pancreaticobiliary diseases, but postendoscopic retrograde cholangiopancreatography pancreatitis (PEP) can be a fatal adverse event. Evidence suggests that statins may exhibit suppressive effects on inflammation in the pancreas. We carried out an observational cohort study to examine the protective effect of statins on PEP. Study: We retrospectively identified consecutive patients who underwent endoscopic retrograde cholangiopancreatography at a tertiary care center in Japan between January 2010 and January 2019. The incidences of PEP were compared between regular and nonregular statin users. Using the multivariable logistic regression model, we examined the association of regular statin use with the incidence of PEP controlling for potential risk factors for PEP. Results: We included 2664 patients (328 regular statin users and 2336 nonregular users). The incidence of PEP did not differ by statin use status ( P =0.52): 8.8% in regular statin users and 7.9% in nonregular users. The multivariable-adjusted odds ratio for PEP comparing regular statin use with nonregular use was 1.08 (95% confidence interval, 0.67-1.72; P =0.76). When we examined specific statin types (hydrophilic and lipophilic statins), we consistently observed the null association: 6.8% of 132 hydrophilic statin users and 10% of 196 lipophilic statin users ( P =0.74 and 0.27, respectively, compared with nonregular users). Conclusions: Regular statin use was not shown to be protective against PEP. A further investigation is warranted before this medication is tested in prospective randomized trials. Abstract : Supplemental Digital Content is available in the text.